Modeling and visualization of receptor clustering on the cellular membrane - Falk, M.; Daub, M.; Schneider, G.; Ertl, T. (2011 IEEE Symposium on Biological Data Visualization, 2011)
In cell biology, apopotosis is a very important cellular process. Apopotosis, or programmed cell death, allows an organism to remove damaged or unneeded cells in a structured manner in contrast to necrosis. Ligands bind to the death receptors located on the cellular membrane forming ligand-receptor clusters. In this paper, we develop a novel mathematical model describing the stochastic process of the ligand-receptor clustering. To study the structure and the size of the ligand-receptor clusters, a stochastic particle simulation is employed. Besides the translation of the particles on the cellular membrane, we also take the particle rotation into account as we model binding sites explicitly. Glyph-based visualization techniques are used to validate and analyze the results of our in-silico model. Information on the individual clusters as well as particle-specific data can be selected by the user and is mapped to colors to highlight certain properties of the data. The results of our model look very promising. The visualization supports the process of model development by visual data analysis including the identification of cluster components as well as the illustration of particle trajectories.